Indoor outdoor effect of antenna diversity on capacity and performance - Chong, Man Lung (Universiti Malaysia Sarawak, UNIMAS, 2009)
Antenna diversity is widely used to improve the transmission signal of wireless communication. In urban area, buildings are built closely and indoor diversity antenna is needed in order to improve the signal reception quality. Instead of using only one omnidirectional antenna, diversity antenna is used to increase the gain and the directivity of antenna. There are antenna diversity techniques used in wireless communication such as spatial diversity, polarization diversity and pattern diversity. Most of the time these diversity techniques are used together to further improve the transmission performance. Considering the very wide usage of diversity antenna for indoor and outdoor applications, this project describes the effect of indoor and outdoor antenna diversity to capacity and performance on wireless communication systems . The performance of indoor diversity antenna is studied by comparing the connection speeds and the coverage range of t he wireless ro uter that operate using one antenna, two antennas and without antenna . Narda, the E lectromagnetic R adiation S urvey M eter is used to measure the field strength of base station antenna in order to study the outdoor per formance of diversity antenna. From the results of this project, proven that antenna diversity improve the capacity and performance of wireless communication systems . With increase of number or diversity antennas place at optimum distance apart, antenna diversity techniques can be used together in wireless communications to improve the quality of the wireless communication systems.